2008
DOI: 10.1016/s0030-6657(08)70287-7
|View full text |Cite
|
Sign up to set email alerts
|

Nowotwory złośliwe jam nosa i zatok przynosowych w materiale własnym – charakterystyka epidemiologiczna i kliniczna

Abstract: (1) The SNM present as a very heterogeneous group of tumors. (2) The most common SNM are a Squamous cell carcinoma, and malignant lymphoma. (3) The majority of SNM are diagnosed at then advanced stage of local disease. (4) The calculated probability of 3-years survival was 64.0%, and 5-years survival 45.0%. (5) The diagnostic, as well as therapeutic approach to SNM requires a multidisciplinary cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is also noteworthy that concomitant chemoradiation therapy is recommended to enhance therapeutic outcome in patients with aggressive local craniofacial malignant tumors (25). Further randomized controlled clinical trials with an adequate sample size are needed to standardize the treatment approach for the treatment of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that concomitant chemoradiation therapy is recommended to enhance therapeutic outcome in patients with aggressive local craniofacial malignant tumors (25). Further randomized controlled clinical trials with an adequate sample size are needed to standardize the treatment approach for the treatment of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly they are diagnosed at an advanced stage due to non-specific symptoms at the initial phase of growth. Differences in histopathological type, site of origin, growth pattern, involvement of neighboring structures and presence of metastases influence the prognosis, which has been regarded as generally poor [4, 5]. Surgical resection is the most effective treatment modality in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Zyłka S, Bień S, Kamiński B, Postuła S, Ziołkowska M. 6 et al on cases, age range from 8 to 82 years .They found maximum patient (59.8%) ,both males and females, in the age above 60 years, among which most common age group 71-80 years(33.3%). Where as minimum concentration was seen in our study over 71-80 years, might be due to lack of awareness, poor socioeconomic conditions .…”
Section: Discussionmentioning
confidence: 98%
“…Dubey SP et al 8 1999 reported 50 malignant tumors of the nasal cavity and paranasal sinuses that were managed in Papua New Guinea from 1986 to 1995. Twenty-nine of these arose in the maxillary sinus, 15 in the nasal cavity, four in the ethmoid sinus and two in the frontal sinus.The study conducted by Zyłka S, Bień S, Kamiński B, Postuła S, Ziołkowska M. et al on 87 cases 6 ,most common defined 22ocalization was maxillary sinus(33.3%). But in 37.9% of cases, due to very advanced stage at time of diagnosis the precise localization within the region was not possible to define.…”
Section: Discussionmentioning
confidence: 99%